2009
DOI: 10.1080/09602010802091829
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation of the updating sub-component of working memory in schizophrenia: A case study

Abstract: Working memory problems have been identified as a core cognitive deficit in schizophrenia. In this paper, we present the results of a cognitive rehabilitation programme (Duval & Coyette, 2005) administered to a schizophrenia patient, and specifically designed to improve the updating sub-component of working memory. The original feature of this programme was that it involved two types of updating exercises: cognitive and ecological. The purpose was to enable the patient to acquire cognitive strategies that alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
0
13
0
2
Order By: Relevance
“…Also, these remediation effects are durable up to at least 6 months after the interventions are withdrawn. Finally, and most importantly, these neuropsychological gains translate to improvements in real-world activities (Larøi and Van der Linden, 2007; Levaux et al, 2009; Medalia and Choi, 2009). Similarly, cognitive remediation programmes address prominent, complementary functional domains such as social cognition – and studies have furthermore observed beneficial effects on functional outcome measures in patients post-treatment (for reviews see Couture et al, 2006; Penn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Also, these remediation effects are durable up to at least 6 months after the interventions are withdrawn. Finally, and most importantly, these neuropsychological gains translate to improvements in real-world activities (Larøi and Van der Linden, 2007; Levaux et al, 2009; Medalia and Choi, 2009). Similarly, cognitive remediation programmes address prominent, complementary functional domains such as social cognition – and studies have furthermore observed beneficial effects on functional outcome measures in patients post-treatment (for reviews see Couture et al, 2006; Penn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Also, these remediation effects are durable up to at least 6 months after the interventions are withdrawn [168]. Finally, and most importantly, these neuropsychological gains translate to improvements in real-world activities [169][170][171]. Similarily, cogni tive remediation programmes address prominent, complementary functional domains such as social cognition -and studies have furthermore observed beneficial effects on functional outcome measures in patient's posttreatment [172,173].…”
Section: Alternatives For Use Of Ce-drugsmentioning
confidence: 99%
“…Prenant en compte l'importante hétérogénéité des déficits cognitifs et des difficultés dans la vie quotidienne, cette approche se fonde essentiellement sur une méthodologie en cas uniques. Dans une première étude publiée [39], un patient schizophrène présentait un déficit spécifique de mise à jour en mémoire de travail (à savoir une difficulté à modifier de façon flexible et continue le contenu de la mémoire de travail en fonction de l'arrivée de nouvelles informations). Ce déficit a été mis en relation avec les difficultés rencontrées par le patient dans sa vie quotidienne : suivre une conversation ou une émission de radio, comprendre le déroulement d'un récit lu.…”
Section: Approche De Remédiation Cognitive Individualisée Et Centrée unclassified